Manajemen Dakwah Mangkunagoro IV - Puput Mulyono; Singgih Purnomo (Lembaga Pengembangan Kinerja Dosen, 2025)
As an umaro who contributed to the revival of Javanese culture, especially in the field of literature, Mangkunagoro IV was referred to as an umaro and ulama. Wedhatama fiber is the work of Mangkunagoro IV which is a form of Mangkunagoro IV's concern and sensitivity to the state of society at that time which experienced a moral crisis due to the entry of foreign cultures, so that Mangkunagoro IV wrote many ethical teachings in accordance with the personality of the Javanese people. This community service seeks to identify the concept of Mangkunagoro IV Da'wah Management. This community service uses participations reports. Mangkunagoro IV had a close relationship with the three previous rulers in the religious field.